Radiant Heat Conduction of Air Plasma in Presence of Alkaline Elements - L. E. Sandrigailo (Наука и техника)
The paper presents results concerning calculations of radiating heat-conduction factor for air plasma in presence of impurities of Na, K, Li, Cs elements.